Chemical risks and risk management measures of relevance to crop production with special consideration of salinity - Qadir, M.; Drechsel, Pay; Salcedo, F. P.; Robles, L. P.; Ben-Gal, A.; Grattan, S. R. (2023)
Improving water quality in agriculture often depends not only on technical solutions but also on effective incentive structures that motivate change. This section examines how economic, regulatory, and institutional incentives can drive better water quality outcomes by encouraging farmers and land managers to reduce pollution at its source. It highlights a variety of approaches used in high-income countries, including pollution taxes, subsidies, payments for ecosystem services (PES), and certification schemes. These tools can be designed as either voluntary or mandatory and are most effective when aligned with measurable environmental outcomes and supported by strong institutional capacity. Examples from New Zealand, Denmark, France, and Canada demonstrate how context-specific incentive systems such as nutrient trading, cooperative contracts, or integrated watershed management can improve agricultural practices while balancing stakeholder needs. The document emphasizes that successful incentive programs require clear objectives, performance monitoring, community engagement, and long-term commitment to ensure sustained impact on water quality.